1967
DOI: 10.1128/aem.15.6.1427-1430.1967
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Glucose by Proliferating Cells of Desulfotomaculum nigrificans

Abstract: Desulfotomaculum nigrificans degraded glucose to acetate, ethyl alcohol, and carbon dioxide. By use of '4C-glucose labeled at different carbon atoms, two pathways of glucose metabolism were detected. They were the Embden-Meyerhof and the Entner-Doudoroff schemes. Because the observed quantities of acetate and carbon dioxide, arising from glucose, were greater than the expected theoretical values, individual fermentations were conducted with 15 uniformly labeled "4C-amino acids. The results indicated that amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Later, Starkey (1938) renamed it to “ Sporovibrio desulfuricans” [ 3 ] before it was finally renamed as D. nigrificans [ 1 ]. D. nigrificans is a moderate thermophile that typically grows with fructose and glucose coupled to sulfate reduction [ 1 , 4 ]; without sulfate, only growth with fructose was observed. Utilizing sugars is rare among Desulfotomaculum species.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Starkey (1938) renamed it to “ Sporovibrio desulfuricans” [ 3 ] before it was finally renamed as D. nigrificans [ 1 ]. D. nigrificans is a moderate thermophile that typically grows with fructose and glucose coupled to sulfate reduction [ 1 , 4 ]; without sulfate, only growth with fructose was observed. Utilizing sugars is rare among Desulfotomaculum species.…”
Section: Introductionmentioning
confidence: 99%
“…These results and the favourable energy release compared with the criterion both support the stoichiometry of reaction lk for the partial oxidation of glucose. Akagi and Jackson (1967) did, however, note that little «0•1 %) labelled glucose was incorporated as cell carbon, suggesting that, like the substrates set out in Table 2, glucose acts as an energy but not a carbon source; this is in contrast to the other five substrates in Table 1 which apparently supply cell carbon as well as energy. Table 2 illustrates the oxidation of five substrates which provide energy, but not cell carbon, for the growth of sulphate reducers.…”
Section: =-mentioning
confidence: 93%
“…However, Postgate (1951Postgate ( , 1953 demonstrated growth of D. vulgaris (Hildenborough strain) on glucose, and when resting cells of D. desulfuricans were used the presence of enzymes of the Embden-Meyerhoff-Parnes pathway was reported (Anderson et al 1958). Akagi and Jackson (1967) showed that growing cells of Desulfotomaculum ntgrificans degraded glucose to acetate, ethanol and carbon dioxide, primarily via (1951,1953), Akagi and Jackson (1967) U Notes C 2,3 2,3 2,3 3 4…”
Section: (4) Combination Of Sulphate Reduction and Oxidation Of Complmentioning
confidence: 99%
“…The D. nigrificans strain was cultivated on a TSI medium (Triple Sugar Iron Agar, BBL BD Biosciences Sparks) with the following composition (quantities given per 1 L of purified water): 10 g enzymatic casein hydrolysate, 10 g peptone, 5 g sodium chloride, 10 g lactose, 10 g sucrose, 1 g glucose, 0.2 g ferrous ammonium sulfate, 0.2 g sodium thiosulfate, 0.025 g phenol red, 13 g agar at a temperature of 37°C, for a period of 72 h, under anaerobic conditions, with the use of a Genbox anaer generator (bioMerieux). To obtain semiliquid medium, the primary medium was diluted three times.…”
Section: Methodsmentioning
confidence: 99%